Prevalence of Retinopathy of Prematurity in Premature Neonates Visiting Sir Gangaram Hospital Lahore - Abdul Rauf, Huma Kayani Saigol, Khurram Chauhan, Seemab Akbar, Najam Iqbal Chaudhary (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Retinopathy of prematurity (ROP) is a serious problem which affects the premature infants. It is becoming a public health issue in developing countries like Pakistan. Antenatal visits, delivery and NICU management plays an important role in prevention of ROP. Objective: The aim of this study was to find out the prevalence of retinopathy of prematurity in premature neonates visiting Sir Ganga Ram hospital Lahore. Study Design: observational study. Settings: Study was carried out in Out-patient of Ophthalmology Department, A public sector Sir Ganga Ram Hospital, Lahore Pakistan. Duration: The duration of the study was one year from September 2020 to August 2021. Methods: All the preterm babies referred from pediatric department were part of study. A total of 160 babies were examined in this study. The data was presented in the form of frequency and percentages using SPSS software. Results: In this study out of 160 patients 75(46.87%) were male and 85(53.12%) were females. The prevalence of retinopathy of prematurity was observed in 43(26.87%) babies. Weight of patients less than 1kg was 11(25.58%) between 1-1.5 kg was noted in 28(65.11%) patients and >2 kg weight was noted in 4(9.30%) patients. Babies with ROP, 23(53.48%) recovered without any intervention, 9(20.93%) required intervention and recovered after 3 months follow up, 6(13.95%) kept under observation and recovered after 4 months and 5(11.62%) babies lost follow up. Practical implication: this study will help in early diagnosis and prevention of disease and help to formulate and introduce newer guidelines for prevention, early identification and prompt treatment starting from basic levels to prevent development of ROP of any stage. Conclusion: The study concluded that the prevalence of retinopathy of prematurity in premature neonates visiting Sir Ganga Ram hospital Lahore is 27%. Keywords: Retinopathy of Prematurity(ROP), Neonates, Preterm, screening, blindness